Impact of code stroke on thrombolytic therapy in patients with acute ischemic stroke at a secondary referral hospital in Taiwan. Issue 11 (November 2018) - Hsiao, Cheng‐Lun; Su, Yu‐Chin; Yang, Fu‐Yi; Liu, Chih‐Yang; Chiang, Han‐Lin; Chen, Guei‐Chiuan; Hsu, Po‐Jen; Chen, Pei‐Ya; Lin, Shinn‐Kuang
Abstract : Background: : Efficacy of thrombolytic therapy decreases with time elapsed from symptom onset. We sought to identify the impact of code stroke on the thrombolytic therapy. Methods: : Code stroke is activated by the emergency physician when a patient is eligible for thrombolytic therapy. We retrospectively reviewed patients with acute ischemic stroke between January 2011 and December 2014. Results: : In total, 1809 patients were enrolled. Code stroke was activated in 233 of 351 patients arriving at the emergency room (ER) within 3 h of symptom onset, and in 21 patients arriving >3 h. The sensitivity, specificity, and positive and negative predictive values of code stroke were 76%, 46%, 72%, and 51%, respectively. Thrombolytic therapy was provided to 58 patients, accounting for 3.4% of all cerebral infarcts. Code stroke was activated in 40 of these patients. The most common reasons for excluding thrombolytic therapy were: National Institute of Health Stroke Scale (NIHSS) < 6, intracranial hemorrhage (ICH), and age >80 years. Mean liaison‐to‐neurological evaluation time was only 6 min. Code stroke activation significantly reduced all the intervals, except for the onset‐to‐ER and door‐to‐order times. During the 4‐year study period, there were significant reductions of the door‐to‐neurology liaison time by 28 min and door‐to‐laboratory time by 22 min. The proportion of door‐to‐needle time within 60 min improved from 33% in 2011 to 67% in 2014. Improved NIHSS scores during hospitalization were most prominent in tPA‐treated patients. Symptomatic ICH occurred in 3.6% patients arriving within 3 h. Death occurred in 50% of patients received tPA treatment on family's request, and only 13% of those patients had favorable outcome. Conclusion: : Code stroke is effective in reducing in‐hospital delays. The accuracy of code stroke activation has acceptable sensitivity but low specificity. Rapid patient assessment by neurologists increases the number of patients eligible for thrombolytic therapy.